The social construction of vocational education - possibilities for change towards status improvement - Höhns, Gabriela [Verfasser] (My University, 2024)
„This article explores change possibilities towards status improvement in vocational education’s social construction. Following other researchers, it assumes that higher-status vocational education should give vocational learners perspectives that would accord with their identities and desires, broadly ranging between working in a particular company and further studies. The article proposes that change in this direction must concern the transmitter-acquirer-knowledge-relation and also curriculum, evaluation and the external relations of education. To think systematically about changes of these ‘adjusting screws’, this article proposes a realist approach with Bernstein’s conceptual language, and Moore's Bernstein-based model of education where vocational learners, plausibly, receive an orientation towards broad futures beyond narrow job roles. Moore's model implies fundamental changes of all these ‘adjusting screws’ and, importantly, of the principle underlying their realisation in schools. The case of company-based education in Germany’s ‘dual system’ is advanced as a real-life example for the highly theoretical model. Findings from a Bernsteinian analysis of the transmitter-acquirer-relation in regulated company transmission made sense, when the system was understood as realising the principles envisioned in Moore’s model. The model and its underlying principles, together with their realisation in the DS, open up a perspective towards education (instead of job training) in workplaces.“ (author’s abstract; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; T 2.1 Bildungstheorien; 370; 300; Berufsbildung; Duales System; Attraktivität; Bildungstheorie; Modellierung; Bernstein, Basil